Lifestyle Behaviors, Perceived Stress, and Inflammation of Individuals With Chronic Graft-Versus-Host Disease. Issue 1 (January 2018) - Lynch Kelly, Debra; Lyon, Debra E.; Periera, Deidre; Garvan, Cynthia; Wingard, John
Abstract : Background: Stress is a potent immunomodulator contributing to chronic conditions. Chronic graft-versus-host disease (cGVHD) is a life-threatening late effect of allogeneic hematopoietic cell transplantation associated with stress and exaggerated immune response that may be associated to lifestyle behaviors. Objective: The aim of this study is to explore associations among lifestyle behaviors, perceived stress, and inflammation of individuals with cGVHD. Methods: A secondary analysis from a prospective observational study of 24 adults (≥18 years) with cGVHD was conducted. Demographic, clinical, and symptom data were assessed using medical records and validated self-report measures; inflammatory markers were assessed using multiplex and enzyme-linked-immunosorbent assays from plasma. Results: Spiritual growth and total perceived stress were correlated ( P < .001). Nutrition and C-reactive protein were negatively correlated ( P = .02). Physical activity and cytokines (interleukin [IL]-2, IL-4, IL-5, IL-7, IL-10, IL-12, IL-13, IL-17, and granulocyte colony-stimulating factor) were associated ( P < .05). Perceived stress and inflammatory markers were not associated. Individuals did not routinely engage in assessed health-promoting lifestyle behaviors. Conclusion: Associations in this sample were noted among lifestyle behaviors, perceived stress, and inflammation. Given these promising findings, further research with a larger sample size is needed to test these associations. Activity, nutrition, stress management, and social support interventions may reduce stress and inflammation. Particularly, connecting with one's higher-self may reduce levels of perceived stress. Finding ways to engage survivors in healthy lifestyle behaviors should be explored. Implications for Practice: Information from this study allows nurses to be informed about the role of lifestyle behaviors on inflammation and stress to provide anticipatory guidance to HCT survivors regarding lifestyle choices that may mitigate inflammation and stress to promote positive health outcomes.